If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 = 2w * w Multiply w * w 24 = 2w2 Solving 24 = 2w2 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-2w2' to each side of the equation. 24 + -2w2 = 2w2 + -2w2 Combine like terms: 2w2 + -2w2 = 0 24 + -2w2 = 0 Add '-24' to each side of the equation. 24 + -24 + -2w2 = 0 + -24 Combine like terms: 24 + -24 = 0 0 + -2w2 = 0 + -24 -2w2 = 0 + -24 Combine like terms: 0 + -24 = -24 -2w2 = -24 Divide each side by '-2'. w2 = 12 Simplifying w2 = 12 Take the square root of each side: w = {-3.464101615, 3.464101615}
| 2z-13=z+12 | | 7.38=2*3.14*r | | 4x+28=180 | | 3x+7=x+21 | | 2(3+1)= | | 6m-5=3m-4 | | 5y-1=7y-11 | | .06x+.02(40)=.04(x+40) | | 2y=0.5x+7 | | 5y+1=6y-8 | | 5y+1=7y+8 | | 36=4m | | 6x^4-7x^2=3 | | 2x+2x=16 | | 6p=48 | | 3x*-5x= | | 65-6x=21x+17 | | 10-7x=48-21x | | 2x+7-100x=0 | | 64x^2+12x-1=0 | | 4(3x+2)=26 | | 25-7*(x+1)=4 | | 3x+14=86-5x | | 11+2=17 | | 3x+21=13x-89 | | 5x-7+9= | | 6x-1=14-73 | | 6x-1=14-73x | | 11-4a-9a= | | 3x+26=10x-44 | | 5a-7a+8b= | | 7a+4b+5a= |